Leadership and command on the Eastern Front (1941-1945) : the military style of Marchal Konstantin Rokossovskiy - Walsh, S. M. (Department of Applied Science, Security and Resilience, 2010)
Marshal Konstantin Konstantinovich Rokossovskiy, Hero of the Soviet Union, Order of Victory, Knight of the Bath, OBE, victor of Moscow, Stalingrad, Kursk, the destruction of German Army Group Centre and East Prussia, participated in some of the most significant operations in the history of war, let alone the twentieth century. Yet, in the English speaking world Rokossovskiy is unknown, a name, vaguely associated with famous events. There is no sustained historical analysis of Rokossovskiy’s style of leadership and operational command in the English language. Rokossovskiy rejected the authoritarian leadership culture of Stalin’s Soviet Union and Zhukov’s Red Army. Rokossovskiy was highly demanding and occasionally harsh but his leadership encouraged initiative, consultation, trust, delegation and tolerated mistakes in a way that made him unusual, indeed exceptional, in the Red Army. It was primarily an authoritative style of leadership but Rokossovskiy practised different forms and styles of leadership guided by his own instinctive judgement according to the demands of the situation and the nature of his subordinates. This was a considered philosophy of leadership and command that set him apart from his contemporaries. Rokossovskiy’s style of leadership was intimately connected to his conduct of operations. As one of the Red Army’s finest commanders, respected by the Wehrmacht and the Red Army, Rokossovskiy’s operational art was dominated by the idea of depth. Rokossovskiy, the Pole, was the heir to a long Russian tradition, centuries old, of deep operations, whereas Zhukov, the Russian, was committed to operational encirclement and annihilation, a Germanic concept. Marshal Konstantin Konstantinovich Rokossovskiy had a distinct military style of his own: his style of leadership challenged the Red Army’s authoritarian culture whilst his style of operations endorsed the historical traditions of the Russian army. It makes him one of the most significant military commanders of the twentieth century.